Hydrothermal synthesis of α-SnWO4: Application to lithium-ion battery and photocatalytic activity. Issue 7 (1st April 2021) - Alharthi, Fahad A.; Shashank, M.; J, Shashikanth; R, Viswantha; Alghamdi, Abdulaziz Ali; Algethami, JariS.; Alsaiari, Mabkhoot A.; Jalalah, Mohammed S.; Ganganagappa, Nagaraju
Abstract: The high capacity anode material is required to replace the most commonly used anode - graphite to keep up the global demand to achieve the goal. Multi-metal oxide has gained keen attention for its higher theoretical capacity and relatively stable than a single metal oxide. α-SnWO4 has a theoretical capacity of 850 mAh g −1 which is greater than graphite (372 mAh g −1 ). α-SnWO4 has been synthesized through low-temperature hydrothermal method using tin chloride and sodium tungstate as a precursor in acidic medium (succinic acid) at 200 °C for 12 h. The obtained product has been characterized using various analytical tools such as XRD, FT-IR, UV-DRS, BET, PL, SEM, and HR-TEM. XRD analysis shows the orthorhombic phase with a crystallite size of 25 nm α-SnWO4 has been examined as an electrode material for Li-ion battery (LIB) and displays an initial discharge capacity of 985 mAh g −1 . Columbic efficiency close to 100% has been observed for 100 cycles. The stability of the electrode material was studied at different C-rates. Band-gap calculated using UV-DRS (Eg = 1.9 eV) shows that α-SnWO4 is a good candidate for photocatalytic degradation. Results of the photocatalytic experiment using methylene blue (MB) as a model pollutant in an aqueous medium shows good results. The above applications show that α-SnWO4 is multifunctional materials for diverse applications.